Synthetic Methods in Fictional Dialogue in Arabic Poetry - Morad, Ruqhayyah Hesen; Kadhim, Zaineb Ali (Journal of Ecohumanism, 2024)
The sentence is one of the most important components of speech in the Arabic language and other languages. It is the smallest structural unit that includes a meaning. The sentence, as Al-Jurjani mentioned: ((is a compound of two words, one of which is attributed to the other, whether it is useful, such as saying: Zaid is standing, or not, such as saying: If he honors me, it is a sentence that does not benefit except after the arrival of its answer, so the sentence is more general than speech in general)), so according to the previous definition, the sentence is several words that are linked together to produce a new meaning that differs from the meaning of the individual words. The Arabs divided sentences after tracing and induction of the speech of the Arabs into three types: nominal, verbal, quasi-sentence.